The role of peer reward and punishment for public goods problems in a localized society - Hiroki Ozono (Nature Portfolio, 2020)
Abstract Cooperation in social dilemmas can be sustained if individuals are effectively rewarded or punished from peers within the group. However, as group size increases, we inevitably face localization, in which a global group is divided into several localized groups. In such societies, members can reward and punish only neighbors within the same localized group, while cooperation for social dilemmas should be solved through global group involvement. In this situation, the global group and the local group are not always equal in terms of welfare, and situations can arise in which cooperation is beneficial for the global group but not for the local group. We predict that in such a locally inefficient situation, peer reward and punishment cannot function to sustain global cooperation. We conducted an experiment in which 16 group members played a public goods game incorporating peer reward and punishment. We manipulated the range of peer reward and punishment (only local members/all global members) and payoff structure (locally efficient/locally inefficient). We found that high cooperation was not achieved and that peer reward and punishment did not function when, and only when, the group was divided into localized groups and the payoff structure was locally inefficient.